2013
DOI: 10.7763/ijmlc.2013.v3.286
|View full text |Cite
|
Sign up to set email alerts
|

Wi-Fi-Based Localization in Dynamic Indoor Environment Using a Dynamic Neural Network

Abstract: Abstract-Recently, there is an increasing interest in WIFI positioning systems due to the cost and availability of this technology. However, the main problem in WIFI-based localization is the severe fluctuation of received signal strength even for a static client. In this paper, we consider the localization of a wireless device using a dynamic neural network. Many types of dynamic neural networks are simulated, and then we will choose the one that gives best estimations to do real experiments. The proposed app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The research of device and neural network positioning algorithms will be more and more in the future. [20,21]…”
Section: Three-dimensional Positioningmentioning
confidence: 99%
“…The research of device and neural network positioning algorithms will be more and more in the future. [20,21]…”
Section: Three-dimensional Positioningmentioning
confidence: 99%
“…For different scenarios, approximation capabilities are tested for Generalized Regression Neural Network, GRNN, and Multilayer Perceptron, MLP. In [16] the different types of NNs are evaluated under various conditions. The authors determine the most reliable and accurate type of NN architecture among: Nonlinear Autoregressive Network with eXogenous, Feed Forward Time-Delay Neural Network and Layer-Recurrent Network.…”
Section: Survey Of Related Workmentioning
confidence: 99%
“…The recorded RSS values through experiment are used to train a feed-forward type of neural network in [10], it is shown that the neural network-based localization method is better than the well-known weighted k-nearest neighbor (KNN) method in term of cumulative distribution function. Three types of dynamic neural network (DNN) which can reduce the impact of non-stationarity of RSS on localization performance are used to localize the wireless device in [11]. By using Gaussian filter to process RSS value and fuzzy clustering to determine the center of radial basis function (RBF), two RBF neural network localization methods are proposed in [12].…”
Section: Introductionmentioning
confidence: 99%